The Shaft Tomb of Menekhibnekau at Abusir – Season of 2007 - Bares, Ladislav (Zeitschrift für ägyptische Sprache und Altertumskunde, 2008)
During the spring season of 2007, the burial chamber (built of large white limestone ashlars and vaulted inside) has been unearthed at the bottom of the main shaft in the Late Period tomb of Menekhibnekau. The inner sides of the chamber, as well as the sides of the outer and inner sarcophagi (made of white limestone and greywacke respectively) are largely decorated with texts and representations in sunk relief, among them personifications of the day and night hours, excerpts from the Book of the Dead, Pyramid Texts, etc. Although the burial chamber has been robbed already in Antiquity, a few items of the original burial equipment have been preserved. In a separate shaft, serving as an embalmers’ cache, a number of large storage vessels have been examined. On nineteen of them, late hieratic and early demotic inscriptions have been found that mention materials used during mummification.